The role of stakeholders in creating memorable tourist experience in Benteng Heritage Museum, Tangerang - Nova Putra, Aditya; Hendra, Hendra; Ayu Wahyuningputri, Rode; Levyta, Farah; Arafah, Willy; Nurbaeti, Nurbaeti (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2022)
Chinese culture has become one of the ethnic diversity in Indonesia. Chinese descendant or self-identity occurs because of the cross-breeding process between ethnic Chinese and local indigenous peoples which is referred to as assimilation. The reasearch aims to discover the process of discovering the tradition of the Benteng museum in the Old Market area in Tangerang, which is the first Chinese museum in Indonesia that has been restored to become a cultural tourist destination. The existence of these invention tradition bore the diversity of culture festival and culinary Chinese descendant today. The initiation of Udaya Halim who was the pioneer of the Benteng Museum which formed for the purpose of preserving the Chinese Descendant culture. This requires support from the stakeholdser so that it can create memorable tourist experience when visiting area. The research methodology used is quantitative, in which questionnaires are distributed to tourist visiting the Old Market area in Tangerang. The result of this research is that cultural diversity has a 99% influence on existing stakeholders and where stakeholders have a role in 63% in an memorable tourist experience.